PENCARIAN OBJEK WISATA BERSEJARAH DI PULAU JAWA MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK - Nadia Ramadhani; Janson Hendryli; Dyah Erny Herwindiati (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
In order to make a image-based search for historical sites in Java, Convolutional Neural Network is used. Not only to make a website which can search historycal sites in Java using image, it also compared two CNN structure. There are two architechture which is used in this paper which is Residual Network and Inception. There are some experiments that were done to establish the best architecture among the two for this aplication. Those experiments showed that inception gave a better result for the application